Impact of Fe3O4, CuO and Al2O3 on the AC breakdown voltage of palm oil and coconut oil in the presence of CTAB - Mohamad, Nur Aqilah; Azis, Norhafiz; Jasni, Jasronita; Ab Kadir, Mohd Zainal Abidin; Yunus, Robiah; Yaakub, Zaini (MDPI, 2019)
This paper presents an experimental study on the AC breakdown voltages of Refined, Bleached and Deodorized Palm Oil (RBDPO) Olein and Coconut Oil (CO) in the presence of conductive (Iron (II,III) Oxide, Fe3O4), semi-conductive (Copper (II) Oxide, CuO) and insulative (Aluminium Oxide, Al2O3) nanoparticles without and with surfactant. The type of surfactant used in this study was Cetyl Trimethyl Ammonium Bromide (CTAB). The volume concentrations range of Fe3O4, CuO and Al2O3 was varied from 0.001% to 0.05%. Transmission Electron Microscope (TEM) was used to characterize the nanoparticles in RBDPO and CO. AC breakdown voltage tests were carried out for RBDPO and CO of which the AC breakdown voltage at 1% probability was determined based on Weibull distribution. It is found that only Al2O3 can improve the average AC breakdown voltage of RBDPO and CO. The AC breakdown voltages at 1% probability for RBDPO and CO can be improved through introduction of Fe3O4, CuO and Al2O3 at certain volume concentrations. Al2O3 provides the highest enhancement of AC breakdown voltages at 1% probability for RBDPO and CO with the highest percentage of improvement can be up to 52%. CTAB has no clear effect on the improvement of AC breakdown voltages of RBDPO and CO based Fe3O4, CuO and Al2O3 nanofluids.